2019
DOI: 10.4081/monaldi.2019.1094
|View full text |Cite
|
Sign up to set email alerts
|

Incidental diagnosis and therapeutic approach of an iatrogenic intra-parenchymal pulmonary intercostal artery pseudoaneurysm: a case report

Abstract: Intercostal artery pseudoaneurysms (IAP) are extremely rare but its sudden rupture represents a life-threatening complication. We report an unusual case of a late intercostal artery pseudoaneurysm, after a video-assisted thoracoscopic surgery, presenting as a large intra-parenchymal lung mass. Diagnosis was made by biphasic computed tomography angiography and contrast-enhanced pulsed-wave doppler ultrasound. To minimize the risk of aneurysm bleeding immediate angiographic embolization was planned and successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Postoperative intercostal artery pseudoaneurysm is a very rare complication. To the best of our knowledge, only two case reports have been reported thus far [ 9 , 10 ]. Kawai et al reported a case who experienced pseudoaneurysm of the 7th intercostal artery after video-assisted right lower lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative intercostal artery pseudoaneurysm is a very rare complication. To the best of our knowledge, only two case reports have been reported thus far [ 9 , 10 ]. Kawai et al reported a case who experienced pseudoaneurysm of the 7th intercostal artery after video-assisted right lower lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases of delayed intercostal artery pseudoaneurysm after thoracoscopy were reported in the English literature. Both cases presented with a large hemothorax after intercostal artery pseudoaneurysm rupture and required surgical attention 13,14 . Conversely to intercostal artery pseudoaneurysm, there are no reports of TDAP after thoracoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the traditional surgical management of pseudoaneurysm has been widely replaced by endovascular approaches 17 . Embolization by metallic coils and other materials such as hemostatic particles, glue, thrombin, polyvinyl alcohol have become generalized 14 . Moreover, US-guided thrombin injection in PA offers an additional interesting minimal invasive option 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Many successful cases have been reported [8, 11, 14-16, 19, 22-25]. Generally speaking, microcoils were the rst choice for embolisation [8,14,15,19,22,14,25], but glue-lipiodol mixture [16], polyvinyl alcohol particles and gelfoam slurry [11,23] could also serve as alternatives. Callaway et al [5] reported a patient cured with covered stent.…”
Section: Discussionmentioning
confidence: 99%